An 'Anglo-Saxon' cup from Gaping Lane, Hitchin. - FITZPATRICK-MATTHEWS, KEITH J.; MORRIS, ISOBEL (Hertfordshire Archaeology & History, 2024)
The article discusses the discovery of an 'Anglo-Saxon' cup from Gaping Lane, Hitchin, which was donated to the Hitchin Museum in 1939. The cup's unique characteristics have led to speculation about its origins, with some suggesting it is Roman or Saxon in nature. The study of this cup sheds light on the transition from Roman to Anglo-Saxon cultural influences in the region, challenging simplistic narratives of conquest and highlighting the complex interactions between different cultural groups in early medieval England. The cup's manufacturing techniques and form suggest a blend of Romano-British and Germanic influences, reflecting a nuanced cultural exchange during this period.